Woodland, cropland and hedgerows promote pollinator abundance in intensive grassland landscapes, with saturating benefits of flower cover. Issue 1 (16th November 2021) - Alison, Jamie; Botham, Marc; Maskell, Lindsay C.; Garbutt, Angus; Seaton, Fiona M.; Skates, James; Smart, Simon M.; Thomas, Amy R. C.; Tordoff, George; Williams, Bronwen L.; Wood, Claire M.; Emmett, Bridget A.
Abstract: Pollinating insects provide economic value by improving crop yield. They are also functionally and culturally important across ecosystems outside of cropland. To understand landscape‐level drivers of pollinator declines, and guide policy and intervention to reverse declines, studies must cover (a) multiple insect and plant taxa and (b) a range of agricultural and semi‐natural land uses. Furthermore, in an era of woodland restoration initiatives and rewilding ideologies, the contribution of woodland and woody linear features (WLFs; e.g. hedgerows) to pollinator abundance demands further investigation. We demonstrate fine‐scale analysis of high‐quality, co‐located measurements from a national environmental survey. We relate pollinator transect counts to ground‐truth habitat and WLF maps across 300 1 km squares in Wales, UK. We look at effects of habitat type, flower cover, WLF density and habitat diversity on summer abundance (July and August) of eight insect groups, representing three insect orders (Lepidoptera, Hymenoptera and Diptera). Compared with improved grassland (the dominant habitat in Wales), pollinator abundance is consistently higher in cropland and woodland—especially broadleaved woodland. For mining bees and two hoverfly groups, abundance is predicted to be at least 1.5× higher in woodland ecosystems than elsewhere. Furthermore, we estimate contributions of WLFs to abundance in agriculturally improved habitats to be up to 14% for honeybees and up to 21% for hoverflies. The abundance of all insect groups increases with flower cover, which is a key mechanism through which woodland, cropland and grassland support pollinators. Importantly, we observe diminishing returns of increasing flower cover for abundance of non‐ Apis pollinator groups, expecting roughly twice the increase in abundance per % flower cover from 0% to 5%, as compared with 10% to 15%. However, the shape of the relationship was inverted for honeybees, which showed steeper increases in abundance at higher flower cover. Synthesis and applications . We provide a holistic view of the drivers of pollinator abundance in Wales, in which flower cover, woodland, hedgerows and cropland are critical. We propose a key role for woodland creation, hedge‐laying and farmland heterogeneity within future land management incentive schemes. Finally, we suggest targeting of interventions to maximise benefits for non‐ Apis pollinators. Specifically, increasing floral provision in areas where existing flower cover is low—for example, in flower‐poor improved grasslands—could effectively increase pollinator abundance and diversity while prioritising wild over managed species. Abstract : We provide a holistic view of the drivers of pollinator abundance in Wales, in which flower cover, woodland, hedgerows and cropland are critical. We propose a key role for woodland creation, hedge‐laying and farmland heterogeneity within future land management incentive schemes. Finally, we suggest targeting of interventions to maximise benefits for non‐ Apis pollinators. Specifically, increasing floral provision in areas where existing flower cover is low—for example, in flower‐poor improved grasslands—could effectively increase pollinator abundance and diversity while prioritising wild over managed species.